Circular Economy Framework for Energy Recovery in Phytoremediation of Domestic Wastewater - Mustafa H.M.; Hayder G.; Mustapa S.I. (MDPI, 2023)
Bioremediation; Growth rate; Life cycle; Tanks (containers); Wastewater treatment; Bio-energy; Circular economy; Energy recovery; Phytoremediation; Phytoremediation technique; Plant-based biomass; Relative growth rate; Wastewater treatment; Biomass